2018
DOI: 10.3390/ijerph15122797
|View full text |Cite
|
Sign up to set email alerts
|

Methods for Evaluating the Combined Effects of Chemical and Nonchemical Exposures for Cumulative Environmental Health Risk Assessment

Abstract: Cumulative risk assessment (CRA) has been proposed as a means of evaluating possible additive and synergistic effects of multiple chemical, physical and social stressors on human health, with the goal of informing policy and decision-making, and protecting public health. Routine application of CRA to environmental regulatory and policy decision making, however, has been limited due to a perceived lack of appropriate quantitative approaches for assessing combined effects of chemical and nonchemical exposures. S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
32
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(32 citation statements)
references
References 92 publications
(123 reference statements)
0
32
0
Order By: Relevance
“…2012 ). Yet, there has been no progress in this regard, with cited reasons including data deficiencies, inherent analytical complexities, lack of mechanistic understanding regarding stressor interactions, and lack of sufficient analytical tools ( Sexton 2015 ; Payne-Sturges et al. 2018 ).…”
Section: Current Environmental Policy Approaches For Neurodevelopmentmentioning
confidence: 99%
See 2 more Smart Citations
“…2012 ). Yet, there has been no progress in this regard, with cited reasons including data deficiencies, inherent analytical complexities, lack of mechanistic understanding regarding stressor interactions, and lack of sufficient analytical tools ( Sexton 2015 ; Payne-Sturges et al. 2018 ).…”
Section: Current Environmental Policy Approaches For Neurodevelopmentmentioning
confidence: 99%
“…2011 ). Calls for federal and state environmental agencies to consider such cumulative risks in regulatory and policy decisions have been made by community advocates, stakeholders, and independent advisory bodies since the 1980s ( NRC 1993 ; National Environmental Justice Advisory Council 2004 ; NRC 2008 , 2009 ; Browner and Hansen 1997 ; U.S. EPA 1986 ), and significant research investments have been made to develop methods to assess the combined effects of multiple chemical and nonchemical exposures ( National Institute of Environmental Health Sciences 2018 ; Payne-Sturges et al. 2018 ; Macdonell et al.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although research products such as health impact assessments or policy analyses can offer real value, EJ communities may struggle to use these products toward structural change without political power, funding, or lasting institutional partnerships ( Bourcier et al. 2015 ; Payne-Sturges et al. 2018 ; Scammell and Howard 2020 ).…”
Section: Resultsmentioning
confidence: 99%
“…In some cases included here, a study successfully identified environmental health risks or community priorities but described only hypothetical next steps toward addressing them (e.g., Quach et al 2015). Although research products such as health impact assessments or policy analyses can offer real value, EJ communities may struggle to use these products toward structural change without political power, funding, or lasting institutional partnerships (Bourcier et al 2015;Payne-Sturges et al 2018;Scammell and Howard 2020).…”
Section: Critique Of "Participation As Benefit" In Ej Contextsmentioning
confidence: 99%